THE RELATIONSHIP BETWEEN OBESITY AND DIETARY INTAKE OF OBESE AND PRE-OBESE FEMALE STUDENTS – AJA CAMPUS HAIL UNIVERSITY - Shommo, Sohair A M.; Aslami, Ibtihaj Mardi A.; Al-Tamimi, Iman R. F.; Anzi, Gamilah F.K.; Al Turki, Rana S.; Al-Tamimi, Khadija M. (European Scientific Journal, ESJ, 2014)
Globally obesity has reached to epidemic proportions, and the people of the Gulf countries have also affected, especially high income, oilproducing countries. Recent data clearly indicate a high prevalence of adult obesity particularly in women in the Kingdom. This paper aims to identify the relationship between obesity and dietary intake of obese and pre-obese female students in Hail University–KSA. Descriptive analytical approach was used in this paper. BMI was calculated and related to dietary intake using food frequency questionnaire. Results shows prevalence of obesity grades was n(%); 43(43%) obesity grade I, 17(17%) obesity grade II, and 8(8%) were grade III obesity. Thirty one subjects were pre-obese and only one subject was overweight. Basic food groups consumption as stated in frequency per week revealed that: female students consumed more servings (>6 times/ week ) of fruits; vegetables; and dairy products, alternatives, sweets and candies, eggs, legumes, rice macaroni and other starch foods, non-alcoholic beverages. Whereas they consumed less servings (≤Once/ week) of breads, fruit juices, carbonated drinks and potato. The majority of the subjects 65% ate chicken with rice (Kabsa) as staple food, whereas 4% ate other starchy food. High consumption of energy dense foods might be responsible for increased deposition of calories in the form adipose tissue. Conclusion: It is crucial to enumerate awareness programs to modify dietary behavior and eating habits of female students and Hail community with respect to food intake. This will be effective in the treatment of obesity, especially in Saudi Arabia.